The genetic susceptibility to type 2 diabetes may be modulated by obesity status: implications for association studies - Charpentier Guillaume; Marre Michel; Balkau Beverley; Potoczna Natascha; Horber Fritz; Choquet Hélène; Nead Kevin T; Cauchi Stéphane; Froguel Philippe; Meyre David (BMC, 2008)
Abstract Background Considering that a portion of the heterogeneity amongst previous replication studies may be due to a variable proportion of obese subjects in case-control designs, we assessed the association of genetic variants with type 2 diabetes (T2D) in large groups of obese and non-obese subjects. Methods We genotyped RETN, KCNJ11, HNF4A, HNF1A, GCK, SLC30A8, ENPP1, ADIPOQ, PPARG, and TCF7L2 polymorphisms in 1,283 normoglycemic (NG) and 1,581 T2D obese individuals as well as in 3,189 NG and 1,244 T2D non-obese subjects of European descent, allowing us to examine T2D risk over a wide range of BMI. Results Amongst non-obese individuals, we observed significant T2D associations with HNF1A I27L [odds ratio (OR) = 1.14, P = 0.04], GCK -30G>A (OR = 1.23, P = 0.01), SLC30A8 R325W (OR = 0.87, P = 0.04), and TCF7L2 rs7903146 (OR = 1.89, P = 4.5 × 10-23), and non-significant associations with PPARG Pro12Ala (OR = 0.85, P = 0.14), ADIPOQ -11,377C>G (OR = 1.00, P = 0.97) and ENPP1 K121Q (OR = 0.99, P = 0.94). In obese subjects, associations with T2D were detected with PPARG Pro12Ala (OR = 0.73, P = 0.004), ADIPOQ -11,377C>G (OR = 1.26, P = 0.02), ENPP1 K121Q (OR = 1.30, P = 0.003) and TCF7L2 rs7903146 (OR = 1.30, P = 1.1 × 10-4), and non-significant associations with HNF1A I27L (OR = 0.96, P = 0.53), GCK -30G>A (OR = 1.15, P = 0.12) and SLC30A8 R325W (OR = 0.95, P = 0.44). However, a genotypic heterogeneity was only found for TCF7L2 rs7903146 (P = 3.2 × 10-5) and ENPP1 K121Q (P = 0.02). No association with T2D was found for KCNJ11, RETN, and HNF4A polymorphisms in non-obese or in obese individuals. Conclusion Genetic variants modulating insulin action may have an increased effect on T2D susceptibility in the presence of obesity, whereas genetic variants acting on insulin secretion may have a greater impact on T2D susceptibility in non-obese individuals.